1999
DOI: 10.1088/0953-2048/12/8/301
|View full text |Cite
|
Sign up to set email alerts
|

Phase and microstructure evolution in the process of the composite Bi-2212-(Sr, Ca)3Al2O6glass-ceramics formation

Abstract: Devitrification of glass with a cation ratio corresponding to the composition {Bi2.1Sr2CaCu2Ox+0.4Sr1.7Ca1.3Al2O6} was studied. At temperatures below 600 °C, the phases crystallized in the order Bi-2201, Cu2O, CaO, (Sr,Ca)3Bi2O6, while Al ions concentrated in the remaining glass. Above 600 °C, Bi-2212 and (Sr,Ca)3Al2O6 formed simultaneously, so that at 750 °C, the two-phase composite Bi-2212-(Sr,Ca)3Al2O6 was obtained that contained grains of the aluminate phase 0.03-0.3 µm in size. The Al-rich phase surplus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…14 c). 208 However, in this case the aluminate grains are partially aggregated in the space between lamellae of the superconducting phase.…”
Section: Microcomposites Based On Phases Of the Bi ± (Pb) ± Sr ± Ca ±...mentioning
confidence: 99%
See 1 more Smart Citation
“…14 c). 208 However, in this case the aluminate grains are partially aggregated in the space between lamellae of the superconducting phase.…”
Section: Microcomposites Based On Phases Of the Bi ± (Pb) ± Sr ± Ca ±...mentioning
confidence: 99%
“…204,205,207 Bi2212-based composites with inclusions of compatible Al-containing oxides have been studied in detail. 164,168,169,208 It was found that the BiSr 1.5 Ca 0.5 Al 2 O z phase is nearly completely segregated in the intercrystalline space of the Bi2212 phase, so that the intergranular electric contacts are broken. At the same time, Sr 1.7 Ca 1.3 Al 2 O 6 mainly forms inclusions inside of the Bi2212 crystallites and, hence, the superconducting current can flow throughout the whole volume of the sample (Fig.…”
Section: Microcomposites Based On Phases Of the Bi ± (Pb) ± Sr ± Ca ±...mentioning
confidence: 99%
“…Different ways of inclusion formation were investigated. For instance, fine precipitates of the secondary phases were created by partial decomposition of the single-phase superconductor [3,6]; MgO was introduced in the form of micro-or nanosize whiskers and grains [5,[7][8][9]; submicron inclusions of complex metal oxides were formed in the Bi-2212 matrix via processing of the homogeneous precursors [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%